2015
DOI: 10.3389/fnins.2015.00266
|View full text |Cite
|
Sign up to set email alerts
|

Decision making and ambiguity in auditory stream segregation

Abstract: Researchers of auditory stream segregation have largely taken a bottom-up view on the link between physical stimulus parameters and the perceptual organization of sequences of ABAB sounds. However, in the majority of studies, researchers have relied on the reported decisions of the subjects regarding which of the predefined percepts (e.g., one stream or two streams) predominated when subjects listened to more or less ambiguous streaming sequences. When searching for neural mechanisms of stream segregation, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
5
0
10
Order By: Relevance
“…Some studies have suggested layer-specific differences in the representation of auditory information along the vertical axis of the auditory cortex (Bandyopadhyay et al, 2010;Li et al, 2014;Tischbirek et al, 2019). In agreement, a growing body of human imaging studies has shown attention and task-related modulation of auditory processing in the A1 (Deike et al, 2015;Häkkinen and Rinne, 2018;Petkov et al, 2004;Puschmann et al, 2017) based on gross neural or metabolic response measures. However, how the canonical principles of the columnar processing are reflected in the aforementioned multiplexed function of the A1 is very much unknown (Ohl, 2015;King et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…Some studies have suggested layer-specific differences in the representation of auditory information along the vertical axis of the auditory cortex (Bandyopadhyay et al, 2010;Li et al, 2014;Tischbirek et al, 2019). In agreement, a growing body of human imaging studies has shown attention and task-related modulation of auditory processing in the A1 (Deike et al, 2015;Häkkinen and Rinne, 2018;Petkov et al, 2004;Puschmann et al, 2017) based on gross neural or metabolic response measures. However, how the canonical principles of the columnar processing are reflected in the aforementioned multiplexed function of the A1 is very much unknown (Ohl, 2015;King et al, 2018).…”
Section: Introductionmentioning
confidence: 93%
“…This pattern of buildup of streaming decisions was not supported, however, by Deike et al (2012) for complex tone stimuli. The ambiguity region of frequency difference may be influenced by more cognitive than sensory factors, such as interpretation of instructions or attentional influences (Carlyon et al, 2001;Micheyl and Oxenham, 2010;Deike et al, 2015). Most studies of auditory stream segregation have focused on the effects of variable stimulus parameters and task demands on the streaming tendencies of normal-hearing listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested layer-specific differences in the representation of auditory information along the vertical axis of the auditory cortex, with granular layers revealing more accurate tonotopic response properties due to the dominant lemniscal inputs compared to supragranular and infragranular layers [13][14][15] . In addition, a growing body of human imaging studies has shown attention and task-related modulation of auditory processing in the A1 [16][17][18][19] based on gross neural or metabolic response measures. However, how the canonical principles of the columnar processing are reflected in the aforementioned multiplexed function of the A1 is very much unknown 9,20 .…”
mentioning
confidence: 99%